Stories of survival Level 3 / Beddall, Fiona. - Beddall, Fiona (Harlow, Essex, England : Penguin Readers, 2011)
"Some people choose adventure. Others suddenly find themselves in danger in their ordinary lives. This book tells the true stories of survivors. In the cold of Antarctica or a small Rwandan bathroom, these people have known terrible suffering - but have lived."--P. [4] of cover.
Keywords: Readers (Adult); Readers for new literates; English language; Reading comprehension; Survival